Multiscale dynamics in star-forming regions: the interplay between gravity and turbulence. Issue 3 (29th November 2019) - Traficante, A; Fuller, G A; Duarte-Cabral, A; Elia, D; Heyer, M H; Molinari, S; Peretto, N; Schisano, E
ABSTRACT: In this work, we investigate the interplay between gravity and turbulence at different spatial scales and in different density regimes. We analyse a sample of 70- μ m quiet clumps that are divided into three surface density bins, and we compare the dynamics of each group with the dynamics of their respective filaments. The densest clumps form within the densest filaments, on average, and they have the highest value of the velocity dispersion. The kinetic energy is transferred from the filaments down to the clumps most likely through a turbulent cascade, but we identify a critical value of the surface density, Σ ≃ 0.1 g cm −2, above which the dynamics change from being mostly turbulent-driven to mostly gravity-driven. The scenario we obtain from our data is a continuous interplay between turbulence and gravity, where the former creates structures at all scales and the latter takes the lead when the critical surface density threshold is reached. In the densest filaments, this transition can occur at the parsec, or even larger scales, leading to a global collapse of the whole region and most likely to the formation of the massive objects.